Critical thresholds for cerebrovascular reactivity after traumatic brain injury - Sorrentino, Enrico; Diedler, Jennifer (Neurocritical care, 2012)
Introduction: Pressure-reactivity index (PRx) is a useful tool in brain monitoring of trauma patients, but the question remains about its critical values. Using our TBI database, we identified the thresholds for PRx and other monitored parameters that maximize the statistical difference between death/survival and favorable/unfavorable outcomes. We also investigated how these thresholds depend on clinical factors such as age, gender and initial GCS. Methods: A total of 459 patients from our database were eligible. Tables of 2 × 2 format were created grouping patients according to survival/death or favorable/unfavorable outcomes and varying thresholds for PRx, ICP and CPP. Pearson’s chi square was calculated, and the thresholds returning the highest score were assumed to have the best discriminative value. The same procedure was repeated after division according to clinical factors. Results: In all patients, we found that PRx had different thresholds for survival (0.25) and for favorable outcome (0.05). Thresholds of 70 mmHg for CPP and 22 mmHg for ICP were identified for both survival and favorable outcomes. The ICP threshold for favorable outcome was lower (18 mmHg) in females and patients older than 55 years. In logistic regression models, independent variables associating with mortality and unfavorable outcome were age, GCS, ICP and PRx. Conclusion: The prognostic role of PRx is confirmed but with a lower threshold of 0.05 for favorable outcome than for survival (0.25). Results for ICP are in line with current guidelines. However, the lower value in elderly and in females suggests increased vulnerability to intracranial hypertension in these groups.